(untitled) (The Journal of Building and Land Development, 2021)
From 2002 to 2012, the populations of Dar-es-Salaam and urban Tanzania, respectively, grew at 6.5% and 5.3%, making Tanzania the fastest urbanizing country in Sub-Saharan Africa. Recent poverty studies on Tanzania indicated rising urban poverty, especially in Dar-es-Salaam city. Increased urban population and poverty result in unplanned informal settlements deteriorating into slums. This study shows that the structural quality of housing reflected significant inequalityin capabilitiesto improve housing and settlement conditions. Despite efforts to improve community infrastructure, the risk of deterioration of informal urban settlements to slums remains. The study surveyed 200 households in Buguruni and Vingunguti wards, in peri-urban Dar-es-Salaam. Fifty key informant interviews supplemented the survey. This article presents an empirical analysis of two settlements, Mnyamani and Kisiwani, with similar housing and settlement conditions. The study aimed to establish (1) the extent of the poor structural quality of housing in the case-study area, and (2) the contribution of urban poverty and inequality to increasing poor structural quality of housing in Dar-es-Salaam city. Findings revealed urban income and non-income poverty and inequalities in the case-study area, causing reduced capabilities to improve housing conditions resulting in the poor structural quality of housing and increased generalized urban poverty and settlement conditions. Keywords: Urbanization, Urban poverty, Structural quality of housing